PEREMPUAN PEMULUNG DALAM MENDUKUNG EKONOMI KELUARGA DI PESISIR TELUK KENDARI - Rommy Rio Kauntu; Rahmat Sewa Suraya (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
The purpose of this study is to describe the activities of scavenger women in supporting the family economy in the coastal bay of Kendari. Marvin Harris's Materialism Theory said that cultural materialism is based on the concept that the material conditions of society determine human consciousness and not vice versa. The research method is the ethnographic method with data collection techniques are observation techniques and in-depth interviews. The data analysis is descriptive qualitative. Data analysis is intended to simplify the data obtained in a form that was easier to read and interpret. The results of the study show that the main reason for women collecting is the low level of education of women scavengers which in the end also has implications for the low capacity of human resource women themselves. In addition, the difficult economic conditions of the family also contributed to the scavenging activities carried out by women in the coastal area of Kendari bay. Keywords: women, scavenger, strategy, contribution, Kendari Bay